KEHIDUPAN MASYARAKAT KELURAHAN SEKARAN TAHUN 1990-2002 - Ratnasari, Diah (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2014)
Sekaran is one village in the District Gunungpati Semarang, precisely located in the village have now itself. This district is the only village in the district Gunungpati which has the function of land to be used as a college. Unnes existence in the Village have now has affected the social life, economy, and culture of the surrounding community. The purpose of this study was to (1) determine the condition of the social life of village communities have now; (2) determine the cultural life of village communities have now years 1990-2002; (3) menegtahui economic life of village communities have now years 1990-2002 or after arrival Unnes. The method used in the form of historical method, which consists of four stages, namely; heuristics, criticism of sources, interpretation, and historiography. Results from this study show that the presence in the village Unnes have now made the region have now become a thriving region. In the social field there has been a increase in education, improving the social status as well as the population growth due to migration as well as the amount of land ownership by the growing immigrant communities. In the field of culture, the culture in such traditions have now begun to fade. Meanwhile, in the aspect of economic life, which have now become a village public welfare increases, the unemployment rate to be reduced. Â